The life-history of Aprosthema tardum (Klug, 1814) (Hymenoptera, Tenthredinoidea, Argidae) - Liston, Andrew D.; Kan, Pieter; Kan-van Limburg Stirum, Brigitte (Contributions to Entomology = Beiträge zur Entomologie, 2018)
Aprosthema species are usually rarely found. In recent years, in southern France, relatively strong populations of A. tardum were detected, which allowed observations on the behaviour and development of the species to be made. The host plant in the study area is Lathyrus latifolius (Leguminosae). As in a few other Aprosthema species, whose development has been previously investigated in northern Europe, A. tardum is bivoltine, although a partial third generation may occur in southern Europe under favourable weather conditions. Adults display seasonal dimorphism, similar to that already described for A. melanurum. Individuals which overwinter make stronger cocoons in the soil (winter cocoons), whereas the more loosely spun cocoons (summer cocoons) of individuals which complete their whole development in a single season are usually found on aerial parts of the host, or plants of other species growing near to the host. The head behind the eyes is more strongly developed in adults which emerge from winter cocoons. A few individuals of A. tardum in the first generation, which normally form summer cocoons, make winter cocoons and enter prolonged diapause, like almost all larvae of the second generation. During oviposition the valvulae 3 are deployed so that their inner surfaces are in very close contact with the leaf epidermis. We suggest that this behaviour is connected to the presence of spines on the valvula inner surface. The latter are found in many argid sawflies, but not in other families of Palaearctic Tenthredinoidea, in which the valvulae have not been observed to be used in a similar way.